Wierność i władza, czyli polityka według Penelopy - Ceglarska, Anna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
So far portrayed above all as a faithful wife of Odysseus, Penelope is a much more complicated character. In fact, her status on Ithaca remains unclear and modern researchers are increasingly inclined to see her as a symbol of a woman who wants to overthrow patriarchal government. This article tries to answer the question of who actually Penelope was and what role did she play during the twenty years of Odysseus’ wanderings. For this purpose, after preliminary discussion on the issue of governance at Ithaca, the evaluation of her relations with other residents of the island was conducted – not only the people, but also Telemachus and, above all, the suitors. For Penelope plays different roles – she is the queen, the mother, the symbol Odysseus’ authority, for some still married, for others a widow. At the same time she remains the most valued and respected person in Ithaca. Due to the analysis of ‘Odyssey’ undertaken in this article and the interpretation of the individual heroes’ behavior, I hope to show on what grounds relied Penelope’s power and whether in fact it can be concluded that she was ruling in the absence of her husband
Keywords: polityka; Penelopa; mitologia grecka; autorytet; zaloty; władza